Why Septic Patients Remain Sick After Hospital Discharge? - Gritte, Raquel Bragante; Souza-Siqueira, Talita; Curi, Rui; Machado, Marcel Cerqueira Cesar; Soriano, Francisco Garcia (Frontiers in Immunology, 2021)
Sepsis is well known to cause a high patient death rate (up to 50%) during the intensive care unit (ICU) stay. In addition, sepsis survival patients also exhibit a very high death rate after hospital discharge compared to patients with any other disease. The addressed question is then: why septic patients remain ill after hospital discharge? The cellular and molecular mechanisms involved in the high rate of septic patient deaths are still unknown. We described herein the studies that investigated the percentage of septic patients that died after hospital discharge ranging from 90 days up to 5 years. We also reported the symptoms of septic patients after hospital discharge and the development of the recently called post-sepsis syndrome (PSS). The most common symptoms of the PSS are cognitive disabilities, physical functioning decline, difficulties in performing routine daily activities, and poor life quality. The PSS also associates with quite often reinfection and re-hospitalization. This condition is the cause of the high rate of death mentioned above. We reported the proportion of patients dying after hospital discharge up to 5 years of followed up and the PSS symptoms associated. The authors also discuss the possible cellular and metabolic reprogramming mechanisms related with the low survival of septic patients and the occurrence of PSS.